RANCANG CAMPURAN BETON MUTU TINGGI DENGAN PENAMBAHAN ADMIXTURE HIGH-SUPERPLASTISIZER DAN RETARDER PADA PROYEK TAMAN ANGGREK RESIDENCE - Rahmawati, Siti; Setia Romadhon, Eri (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2024)
The role of High-Superplasticizer and Retarder is very dominant on the texture and ease of workmanship of high-quality concrete that we expect. High temperatures throughout the concrete journey to the casting site and fast concrete bonding times are the things that are greatly avoided, so the use of certain doses of retarders is a solution to slow the binding time of the concrete itself. Therefore the use of High-Superplasticizer and Retarder needs to be combined well in order to optimize high-quality concrete in terms of workability. In the Taman Anggrek Residence apartment development project, starting from the inspection of aggregate properties then the calculation for the combination of each aggregate is carried out in accordance with the required specifications. The design of the mixture in this study is the Erntroy-Shacklock method with the properties of the material used are as follows; coarse aggregate with a maximum size of 12.5 mm, admixture with trademarks Viscocrete-1003 (High-Superplasisizer) and Plastiment-P121R (Retarder). Testing of concrete compressive strength was carried out at 7, 14 and 28 days. The results showed that at 7 days the average compressive strength was 37,715 MPa (75.43%), 14 days 45,894 MPa (91,788%), 28 days 58.38 MPa (116.76%).